Análise comparativa dos nichos espacial e alimentar de duas taxocenoses de lagartos de áreas de Caatinga e Mata Atlântica de Sergipe - Conceição, Breno Moura da (2014)
A review on the process that governs the structure of assemblages of lizards requires several lines of studies, because there are several forces that can coordinate patterns of resources use. Within intra-population level the variation in the consumption of food items can be generated through individual specialization, this phenomenon is considered as a mechanism that reduces intraspecific competition because populations with a large niche breadth may consist of individuals who use different subsets of available resources. This work is divided into two chapters. The first experiment compared the use of space and food by the lizards in contrasting conditions, and the second assessed the degree of individual specialization of two populations of Tropidurus hispidus. The study was conducted between October/2012 and September/2013 in two areas, the Refugio da Vida Silvestre Mata do Junco (RVSMJ) in the Atlantic Forest, and the Monumento Natural Grota Angico (MNGA) in the Caatinga, both in the state Sergipe. Information about the spatial and food niches and their relationships with ecological and historical factors were used. The assemblages investigated were not structured in relation to the use of space and food resources. Smaller widths and larger niche overlaps (space and food) were observed in general for species in MNGA. Changes in vegetation during the rainy and dry periods provide different opportunities in the use of resources for this assemblage and the high diversity and abundance of species generate competitive pressures that cause greater diversification in the use of resources. In RVSMJ the large amount of resources available and the differences in the ecological aspects of the species show a lack of competition which enable a high niche overlap. The Influence of phylogeny was observed only for the microhabitat use by species in the RVSMJ, showing differences only for historical basal groups (Scleroglossa x Iguania). Adaptations to local conditions and resources were observed for the species Tropidurus hispidus that showed different amplitudes of niches in each area. The highest degree of specialization for individual populations of Tropidurus hispidus occurred in MNGA where this species was more abundant.